Intrapleural fibrinolytic therapy with alteplase in empyema thoracis in children - A prospective pilot study - P K Sharma; B Saikia; R Sharma; P Jain; Z Hussain; P Khilnani (Wolters Kluwer Medknow Publications, 2014)
Objective:outcome of children treated with Intrapleural alteplase therapy in empyema thoracis Design: Prospective interventional pilot study Setting:Pediatric Critical care and Pulmonology unit at Tertiary care Hospital Subjects: All patients of empyema thoracis from 1 month to 18 years of age admitted from May 2012 to April 2014. Method and intervention:Children were selected for intrapleural alteplase therapy and treated under an IRВ (Institutional Review Board) approved protocol.Alteplase (4 mg) was diluted with 50 ml NS and instilled through Intercostal drain(ICD). Chest tube was kept clamped for 1 hour and then opened. The primary outcomes measured were: clinical improvement, lung expansion, ICD days and hospital stay. Secondary outcomes were 24 hour ICD output and adverse effects. Results:A total of 13 patients were given intrapleural alteplase. Median age was 3 years and ranged from 11 month to 14 years. Clinical and radiologicalimprovement was seen in 84.6% (11/13) cases. Fever subsided within 5 days in 54% with median of 4 days (28?days). Respiratory distress settled in median 5 days (2-7 days). ICD days were 6.63±1.8 (mean±SD) days. ICD days after stalling alteplase were 3.45±l .03 (mean±SD) days. Mean hospital stay wasll.27±4.14 (mean±SD) days in successful cases. Mean hospital stay including failure case was 13±5.75 (mean±SD) days.Average flow per day before alteplase was 64.5±65 ml/day which increased to 194.8± 146.3 ml/day with intrapleural alteplase. (P value 0.006). Persistent fever, distress and lung collapse were seen in 15.4% (2/13) cases and both required surgical intervention. Conclusion: Intrapleural alteplase therapy in empyema is beneficial in reducing effusion volume, clinical symptoms, hospital stay, and the need for surgical mtervention.Further large trials are needed for optimum dose, duration of therapy and clamp timing for intarpleural fibniolytic therapy as well as to define relativecontraindications to use of alteplase therapy.